Hedges and Boosters in Academic Writing of ASEAN EFL Learners - Ningrum, Sulistya; Hilda Puspita; Ahmad Iman Mulyadi (Journal of English Education and Teaching, 2024)
Hedges and boosters in general, and academic writing in particular, assume significant role in allowing writers to mitigate opposing claims while strengthening their arguments supported by reliable data. This study aimed to quantify the frequencies of hedges and boosters used by second language (L2) learners of English in ten ASEAN countries, including China, Hong Kong, Indonesia, Japan, Korea, Pakistan, Philippines, Singapore, Thailand, and Taiwan. Research samples were collected from the ICNALE learner corpus comprising 5,400 two different, determined topics of academic writings. Lancsbox 6.0 was utilized to analyse the sample texts. The results elucidate a notable trend wherein ASEAN English as a Foreign Language (EFL) learners exhibit a preference for boosters over hedges Among the identified overused boosters are completely, really, and always, while overused hedges include usually, often, and maybe. This inclination suggests that EFL learners express confidence in articulating their perspectives. Boosters serve as instrumental tools to reinforce confidence and certainty, emphasize significance and relevance, strengthen persuasiveness, enhance coherence and flow, and establish authority and academic voice. Nevertheless, it is imperative for L2 learners to recognize the importance of hedges in denoting tentativeness, softening criticism, acknowledging limitations, and establishing expertise.